Novel treatments for progressive multifocal leukoencephalopathy. (2nd July 2020) - Bennett, Karina M; Fernandes, Peter M
Abstract : Progressive multifocal leukoencephalopathy is a rare demyelinating disorder of the CNS, caused by John Cunningham virus, that occurs in those with impaired immune systems. Existing treatment options are ineffective or unproven. This article reviews research into novel therapies: immune checkpoint-blocking antibodies (nivolumab and pembrolizumab), allogenic BK virus-specific T cell treatment and filgrastim. Results for these therapies in small clinical trials are promising, but further research is required to assess efficacy fully.